Rifampicin induced acute thrombocytopenia with skin rashes: a case report - B. , Loknath; Babu, Venkateswara (International Journal of Advances in Medicine, 2023)
Rifampicin is an essential component of the treatment regimen for tuberculosis. Extensive clinical experience has shown that the drug has mild adverse effect, but on rare occasions, it can cause life threatening adverse reactions like thrombocytopenia. Blajchman et al first described rifampicin-induced thrombocytopenia in 1970. Since then, almost 40 cases have been documented in the literature and a recent review by Cooper and Ghanima included rifampicin in the group of not uncommon drugs that cause immune-mediated thrombocytopenia. Diagnosis of drug-induced immune thrombocytopenia is by identifying clinical symptoms and a careful evaluation of the suspected causative drug. The physician treating tuberculosis patients must be aware of this rare life-threatening complication, when we detected early, is completely reversible.